(untitled) (Lapai Journal of Economics, 2021)
This study examines the impact of debt overhang and crowding out effects hypotheses on investment in Nigeria for the period of 1981 to 2018. A three–stage least squares (3SLS) estimation technique was used after the identification condition was carried out. Simulation was also conducted on the macroeconomic model. The coefficient of the National Income (GDP) is in line with the apriori expectation and also the other explanatory variables. From the results obtained, the variables were stationary at first difference I(1). From the estimated model, all the variable became significant at the 0.05 per cent level. There was no autocorrelation in the estimated model. The simulated results indicate that 10 per cent reduction in the external debt overhang show a negligible impact on investment. When the 50 per cent reduction of external debt overhang was tested, it indicates a higher level impact of 34.18 per cent. Based on these findings, it is therefore recommended that, the government should ensure that external loans are optimally deployed into investment in order to increase the volume of export goods and our National Income so as to enable debt repayment and use the balance to increase the productive investments in the economy.